How work shapes democracy: Political preferences, populist attitudes and far-right voting intentions among the European labour force - a cross-country survey project in the face of the 2024 EU elections - Andreas Hövermann; Bettina Kohlrausch; Arnim Langer; Bart Meuleman (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2025)
In the face of the 2024 European Parliament elections, the study at hand investigates the role of work, working conditions, and workers' voice for (anti-)democratic attitudes and far-right voting intentions. For this purpose, primary survey data was collected among the labour force in ten EU countries (N=15,000). While in all countries, far-right populists obtain sizeable shares of the voting intentions in the data, the majority of respondents in all countries neither intend to vote right-wing nor have voted right-wing in the past and consider the principle of democracy as very important. The world of work is highly relevant when it comes to understanding and combating the rise of the political far right. This study finds consistent and strong evidence that good working conditions and workers' voice provide a buffer against anti-democratic attitudes. Furthermore, concerns about transformations of the labour market play a crucial role for the attitudes towards democracy. Yet, there is no straightforward link with far-right voting intentions: The extent to which democratic attitudes translate into corresponding voting preferences depends on the supply side of the respective party system and the political climate of the country in question. The study closes with proposed instruments towards a fairer and more democratic labour market across the EU.
Keywords: 330